Pengaruh Brand Image, Word of Mouth dan Kualitas Pelayanan: Studi pada Konsumen Keppo Resto Walikukun Ngawi - Bambang Mursito; Raisa Aribatul hamidah; Nikita Damayanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to understand and analyze the influence of brand image, word of mouth and service quality on purchasing decisions (Study on consumers of Keppo Resto Walikukun Ngawi). Keppo Resto Walikukun, Ngawi is the place for this research. This research uses quantitative methodology. This research was conducted for four months. The population in this study were all consumers of Keppo Resto Walikukun Ngawi. The sample in this study consisted of 100 respondents. This research uses probability Sampling. The research results show that brand image, product diversity and service quality have a positive and significant effect on purchasing decisions at Keppo Resto Walikukun Ngawi. based on the results of the coefficient of determination test, brand image, word of mouth and service quality influence purchasing decisions at Keppo Resto Walikukun Ngawi with variables in the model amounting to 10.6%, while the remaining variables amounting to 89.4% are influenced by other factors not taken into account in this research .